Modern recording techniques - Huber, David Miles; Runstein, Robert E. (New York: Focal Press, Taylor & Francis Group, 2014)
"Master the tools and day-to-day practices of music recording and production. Learn the ins and outs of room acoustics and designing a studio. Gain techniques for mic placement and running a session. Get a solid grounding in both theory and industry practice. Modern Recording Techniques, the bestselling, authoritative guide to recording, provides everything you need to improve your craft. Expanded to include the latest digital audio technology, the eighth edition now has sections on touch technology, tablets, and newer connectivity options, such as Thunderbolt. It also includes revamped graphics throughout, and major updates of the sections covering DAWs, MIDI, and mastering. Whether you are just starting out or are looking for a step-up in the industry," -- Publisher's description.
Introduction -- Sound and hearing -- Studio acoustics and design -- Microphones: design and application -- The analog tape recorder -- Digital audio technology -- The digital audio workstation -- Groove tools and techniques -- MIDI and electronic music technology -- Multimedia and the web -- Synchronization -- Amplifiers -- Power and ground related issues -- The art and technology of mixing -- Signal processing -- Noise reduction -- Monitoring -- Surround sound -- Mastering -- Product manufacture -- Studio tips and tricks -- Yesterday, today, and tomorrow.
Includes bibliographical references and index.
Keywords: Sound -- Recording and reproducing; Magnetic recorders and recording; Digital audiotape recorders and recording